Espinha Bífida: perfil sociodemográfico e clínico de brasileiros adultos - Elisângela Maria Soares (2023)
This study represents a first attempt at an epidemiological analysis of the context of adults with Spina Bifida in Brazil. With the improvement of surgical techniques, early correction of spinal cord malformation, use of a ventriculoperitoneal shunt valve and better monitoring of bladder dysfunction, there was a reduction in the morbidity and mortality rate in this population. However, knowledge about the health status and adult health outcomes of people with Spina Bifida is limited. The objective of this study was to analyze the sociodemographic, clinical and rehabilitation profile of Brazilian adults with Spina Bifida, in addition to associating these variables with work. This is an observational, descriptive study with a cross-sectional design, for which a database was built with people monitored in the SARAH Network of Rehabilitation Hospitals. People with Spina Bifida over 18 years of age were evaluated. Data collection occurred with 1673 people through analysis of electronic medical records. Frequency tables were used for the analysis of qualitative variables, and the Shapiro Wilk, Mann Whitney and Chi Square tests were used for other variables. All analyzes were carried out using IBM SPSS version 25 software with a significance level of 5%. The results showed that the majority are women (51.6%), the median age was 25 years old, 46.2% come from the southeast region, 49.1% have secondary education, 91.3% of people are single, with a low percentage of children (6.3%), but women have more children than men (87.4%), there is a small proportion of people in the job market (26.6%). Regarding the clinical and rehabilitation characterization of the participants, the main malformation was myelomeningocele (89.3%), the main affected site was the lumbar/lumbosacral region (67.2%), the vast majority had hydrocephalus (75 .5%), neurogenic bladder and intestine 99.2 and 97.5%, respectively; pressure injuries were identified in most cases (52.1%); pain was representative in this segment of the population (33.9%); participants reported community ambulation (46.6%) and independent ambulation for activities of daily living (70.8%). Regarding the work variable, with sociodemographic, clinical and rehabilitation characteristics, an association was identified between sex, age, education level, marital status, presence of children, diagnosis of Spina Bifida Occulta, location of the malformation, hydrocephalus and locomotion. The results indicate that rehabilitation aimed at the transition from childhood to adulthood must consider the variables studied in this research, aiming at the autonomy and participation of Brazilian adults with Spina Bifida in society.